Carbon Emission Disclosure and Firm Value: A Study of Manufacturing Firms in Indonesia and Australia - Kurnia, Pipin; Nur, D.P. Emrinaldi; Putra, Adhitya Agri (International Journal of Energy Economics and Policy, 2021)
This research aims to examine the effect of carbon emission disclosure on firm value in Indonesia and Australia. Research samples are 39 Indonesian manufacturing firms and 25 Australian manufacturing firms. Firm value is measured by Tobin’s Q while carbon emission disclosure is measured by the carbon emission disclosure index. Based on analysis data, carbon emission disclosure in Indonesia increases firm value. It indicates carbon emission disclosure brings a competitive advantage for firms to create value. On the other hand, there is no effect of carbon emission disclosure in Australia on firm value. Carbon emission disclosure implementation is costly and leads to higher expenses and lower cash flow. Keywords: Carbon Emission Disclosure, Firm Value, Indonesia, Australia JEL Classifications: O16, Q51, Q56 DOI: https://doi.org/10.32479/ijeep.10730